A Viscoelastic Aspiration Technique for Autologous Transplantation of the Free-Flap Inner Limiting Membrane During Macular Hole Surgery. (October 2019) - Hirata, Yuki; Yuda, Kentaro; Odontuya, Davaaadorj; Hayashi, Takahiko; Suzuki, Yasuyuki
Abstract : Supplemental Digital Content is Available in the Text.